F27 Estimation of health state utilities in Huntington's disease: a targeted review. (12th September 2022) - Petrillo, Jennifer; Paret, Kyle; Sawant, Ruta; Koenig, Aaron; Wolowacz, Sorrel; Ronquest, Naoko; Rickards, Hugh
Abstract : Background: Quantifying the impact of Huntington's Disease (HD) on patients' health related quality of life (QoL) is critical to evaluating the disease burden and potential value of new therapeutics. This is often done by estimating health state utilities (HSU), which reflect preferences for various health states. Aims: To evaluate and summarize types of HSU measures used in HD. Methods: A targeted literature review of utility studies in HD was conducted in PubMed. Results: Seven studies were identified across the United States and Europe. The most common generic HSU measures included EQ-5D (N=5) or SF-6D (N=2). Utility estimates decreased with increasing HD severity within studies; however, there was significant variation across studies. EQ-5D reported: mild/prodromal [0.79-0.89], moderate [0.39-0.80], severe/late-stage [-0.11-0.71]. The SF-6D showed similar trends, and estimates were close to those for the age-adjusted normal general population. One study valued health state descriptions (vignettes) for chorea severity stages only while maintaining the same level of overall HD severity. Conclusions: The review identified very large ranges, evidence gaps, and overall uncertainty in validity of existing utility estimates in HD. This suggests limited responsiveness or sensitivity of generic HSU measures to HD symptom changes or differences. While different symptoms in HD (cognitive/motor/behavioral) all have different effects on QoL and may be differentially affected by new treatments, very limited evidence was found for symptom-specific utilities. Further research is needed to better understand preferences and valuation in all stages and symptom clusters of HD, to inform decision-making for new treatments.